PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS KONVENSIONAL DAN TEKNOLOGI INFORMASI OLEH GURU DALAM PROSES BELAJAR MENGAJAR DI SEKOLAH - Al Mahfuz (Jurusan Tarbiyah dan Pendidikan, 2021)
Along with the times in the teaching and learning process in which there is a process of interaction between teachers and students, it is also not free from the influence of the times. In the past, teachers in teaching were sufficient to appear in front of the teaching class using simple methods and media, but it is time now that the description of teaching styles and styles has evolved to be more concise in adapting to the conditions of the development of science and technology that continues to develop. Therefore, teachers must have the knowledge and ability to use both conventional and information technology-based learning media in a collaborative manner so that it makes it easier for students to understand learning material through creative and varied presentations so that it will contribute to student achievement. Keywords: instructional media, conventional, information technology.